There And Back Again: Women’s Marginal Commuting Costs - Stockton, Isabel; Bergemann, Annette; Brunow, Stephan (International Journal of Population Data Science, 2018)
Background Better estimates of workers' willingness to pay to reduce commutes can help evaluate transport policy as well as innovations in workplace organisation implemented by firms (such as telecommuting). These measures could facilitate the employment of workers with care responsibilities by reducing commuting cost. Objectives We estimate female workers' marginal willingness to pay to reduce commuting distance in Germany in a partial-equilibrium model of job search with non-wage job attributes. We consider heterogeneity by parenthood, regional structure and part-time status of workers and are moreover able to explore the role of housing cost, childcare and intra-household interactions for subsamples of the data. Methods and Data We use national insurance data based on a 10% sample of the German labour force including daily information on job spells, personal and job characteristics and residential and workplace post codes between 2000 and 2013 (a customised version of the ``Integrated Employment Biographies'' provided by the Institute of Employment Research, IAB). Taking advantage of the longitudinal structure of the data, our analysis uses a stratified Cox model to take better account of unobserved individual heterogeneity than the previous literature has been able to do. We control for housing costs using additional data on rents at the county level. Findings We find a substantial gender gap in marginal willingness to pay for reduced commuting distance between men and women which is not explained by individual unobserved heterogeneity. When women have their first child, their willingness to pay increases further. Preliminary results suggest that heterogeneity between urban, conurbational and rural areas in Germany plays a minor role in determining women's willingness to pay. Conclusions Substantial gender and motherhood gaps in implicit commuting cost provide an important link between the household and labour market in understanding gender and job choice, with implications for gender-sensitive labour market policy.